Allosteric modulators of human A2B adenosine receptor - Trincavelli, Maria Letizia; Giacomelli, Chiara; Daniele, Simona; Taliani, Sabrina; Cosimelli, Barbara; Laneri, Sonia; Severi, Elda; Barresi, Elisabetta; Pugliesi, Isabella; Greco, Giovanni; Novellino, Ettore; Da Settimo, Federico; et al. (Biochimica et biophysica acta, 2014)
Among adenosine receptors (ARs) the A2B subtype exhibits low affinity for the endogenous agonist compared with the A1, A2A, and A3 subtypes and is therefore activated when concentrations of adenosine increase to a large extent following tissue damages (e.g. ischemia, inflammation). For this reason, A2B AR represents an important pharmacological target. We evaluated seven 1-benzyl-3-ketoindole derivatives (7–9) for their ability to act as positive or negative allosteric modulators of human A2B AR through binding and functional assays using CHO cells expressing human A1, A2A, A2B, and A3 ARs. The investigated compounds behaved as specific positive or negative allosteric modulators of human A2B AR depending on small differences in their structures. The positive allosteric modulators 7a,b and 8a increased agonist efficacy without any effect on agonist potency. The negative allosteric modulators 8b,c and 9a,b reduced agonist potency and efficacy. A number of 1-benzyl-3-ketoindole derivatives were pharmacologically characterized as selective positive (7a,b) or negative (8c, 9a,b) allosteric modulators of human A2B AR. The 1-benzyl-3-ketoindole derivatives 7–9 acting as positive or negative allosteric modulators of human A2B AR represent new pharmacological tools useful for the development of therapeutic agents to treat pathological conditions related to an altered functionality of A2B AR. •We identified allosteric modulators of the human A2B adenosine receptor (A2B AR).•All are unable to bind A2A and A3 ARs and show low or no affinity towards A1 AR.•The new compounds are 1-benzyl-3-ketoindole derivatives.•Small structural differences lead to positive or negative allosteric modulation.•They may help to explore the therapeutic potential of A2B AR allosteric modulators.